(untitled) (Eurasian Journal of Philology Science and Education, 2015)
In article it is a question of art reflection of a sociohistorical stage in G.G.Marquez’s products which having begun with attempts to draw concrete signs of world around of the country, further could create the uniform and generalized vision of all validity of Latin America. Article is intended and can be interesting for laymen, to students and teachers philological faculties, the interested by G.G.Marquez’s creativity, and also the Latin-American literature.